Airpower in Counterinsurgency: Analysis of the Nigerian Air Force’s Response to The Boko Haram Insurgency in the Northeast - ADAMS, DR. JOHN ANYABE; EDET, EFEFIONG ASUQUO; ITAM, MICHAEL R. (Advances in Social Sciences Research Journal, 2021)
This paper examined the role of airpower in counterinsurgency with particular focus on analyzing the Nigerian Air Force’s response to the Boko Haram insurgency in the north-east. The paper adopted the documentary method and sourced data from mainly secondary sources. The Nigeria Air Force ’s operations against the insurgent group commenced in 2010, as part of the armed forces operations within the purview of the Joint Task Force. It was found out that in spite of the significant contribution made by the Nigeria Air Force , there still are challenges to Nigeria Air Force ’s counterinsurgency efforts. Firstly, Nigeria Air Force faces logistical problems such as a dearth of spare parts, shortage of precision-guided ammunition, and inadequate trained personnel that can operate and maintain sophisticated war weapons. Secondly, there is a paucity of systems to initiate and maintain a systematic kill-chain that will encompass searching for the adversary, maintaining intelligence, surveillance and reconnaissance presence over them, and subduing them and obtaining data for purposes of analysis. It was recommended, among others that for the Nigeria Air Force to be more effective in the northeast operations, there should be increased spending on purchasing more modern platforms and weaponry that are pliable in contemporary air power considerations.